DEVELOPING ENGLISH GUIDE BOOK THROUGH SCIENTIFIC APPROACH FOR THE FIRST GRADE OF MA. MIFTAHUL QULUB POLAGAN GALIS PAMEKASAN - Sitti Mukamilah; Ahmad Ahmad; Dewi Pusparini (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
The mastering of English skill has been faced some obstacles for the first students of MA. Mitahul Qulub because some factors, such as: students did not get good guidance to develop their ability, textbook material is not appropriate of students need in the specific institution. Based on the situation, this study aims to develop supplementary English guide book to the student, it includes two English skills both Reading and writing that will be related to the students need and use scientific approach to make a good English book composition. The researcher developed the materials by using some procedures of development  that consisted of some steps of need analysis, material development, expert validation,  revision, try-out, revision II, final product that used questionnaire and interview to collect data. Based on the result of expert validation and try out of materials, it can be concluded that the result of development English guide book is appropriate with the students need and objectives of English guide program itself, exactly the level of students’ difficulties, interest, and standards for the first grade. The experts’ hopes, the book can give a advantages and contribution as supplementary English guide book for the students to develop their English reading and writing skills. The English guide book development consisted of five chapters that provided the materials both reading and writing skills.